Observation of B0s→¯D*0ϕ and search for B0→¯D0ϕ decays; Physical Review D; Vol. 98, iss. 7 - Aaij R. Roel; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen